Experimental Validation of Reinforced Concrete Beam Incorporating Coal Fly Ash and Coal Bottom Ash Using Numerical Analysis - Nurul Natasha, Nasrudin; Nur Farhayu, Ariffin; Aizat, Alias; Abdul Muiz, Hasim; Muhammad Nor Syahrul, Zaimi (Penerbit UTHM, 2023)
The environmental deterioration affected by the disposal of Coal Bottom Ash (CBA) from power stations has worsened as the energy demand has increased. In addition, the increased demand for concrete leads to an increase in aggregate consumption, which contributing to the depletion of natural resources. To prevent the immense amount of CBA waste and the destruction of natural resources, an initiative has been implemented to replace aggregate with CBA in concrete. The Reinforced Concrete (RC) beams underwent a four-pointbending test. The test was done after 28 days of curingage. Therefore, this study was conducted to study the performance of RC beam incorporating CBA as fine and coarse aggregate replacement. The deflection, maximum load and cracking pattern of RC beam were determined. Beam with 100% coarse coal bottom ash 100% fine coal bottom ash resulted to the maximum load at 88 kN with maximum deflection at 18.87 mm. The RC beams were redesigned using the three-dimensional nonlinear simulation software ABAQUS in enable to identify and compare the simulation and experimental findings. The FEA result shows that ultimate load of FEA waswithin 5% range with the experimental results. The simulation results demonstrated that the proposed finite element model accurately predicted the RC beam’s damage behaviour.